PAHAM KEAGAMAAN DOSEN PENDIDIKAN AGAMA ISLAM UPN VETERAN YOGYAKARTA - Achmad Habibullah (Badan Litbang dan Diklat Kementerian Agama RI, 2014)
The map of religious understanding among the Islamic Subject lecturers with respect to the issues of religion and State, religions and tolerance, religion and gender equality, religion and human rights relations has become important bearing in mind their strategic position in the process of transfer of knowledge and internalizing the religious moral values to their students. In the process, religious understanding enclosing their paradigm ofthinking may enter and stain the religious understanding of their students’ facing the conditions of more and more strengthened radical religious understanding. The mapping of religious understanding among the lecturers of Islamic Subject is a case study with a qualitative approach done at UPN Veteran Yogyakarta in 2013. Of the 10 lecturers of Islamic Subject in the university, 7 were interviewed. The study results showed that in general the Islamic Subject lecturers at UPN Veteran Yogyakarta embrace moderate Islamic understanding.